Effect of Severe Plastic Deformation by Extrusion on Microstructure and Physical and Mechanical Properties of Mg–Y–Nd and Mg–Ca Alloys - Luginin N. A. Nikita Andreevich; Eroshenko A. Yu. Anna Yurjevna; Legostaeva E. V. Elena Viktorovna; Schmidt J. Jurgen; Tolmachev A. I. Aleksey Ivanovich; Uvarkin P. V. Pavel Viktorovich; Sharkeev Yu. P. Yury Petrovich (2022, 2022)
Title screen